'Slaves of the Wash-Tub', 1908 (1908)
1908 1880-1914 "'Slaves of the Wash-Tub', 1908" [T0187.jpg], 1908 This article from the 'Saturday Journal' of 22 August, 1908 describes the poor working conditions of laundry-workers in Scotland.